2022
DOI: 10.2147/idr.s380693
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Antimicrobial Prescription at a Tertiary Health Center in Egypt: A Point Survey and Implications

Abstract: Background:The misuse of antimicrobials has major consequences, particularly antimicrobial resistance (AMR) and antimicrobials' related adverse effects. So, the WHO proposed antimicrobial surveillance to improve antimicrobials use. This point prevalence survey (PPS) was conducted to illustrate the prevalence of antimicrobial use at Mansoura University hospitals (MUH), Egypt. Methods: The survey process used was adapted from the European survey of antimicrobial resistance with modifications. The survey was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Regarding other regions in Egypt, Hassuna et al found that 62% of UPEC isolated in Upper Egypt were MDR in 2020 [ 56 ], and a recent study published in 2022 by Mohamed et al reported that 80% of UPEC were MDR in Alexandria governorate, Egypt [ 57 ]. These results reflect the increasing trend of AMR in Egypt, which is strongly linked to poor patient compliance, self-medication, and the availability of antibiotics as over-the-counter medications [ 58 ]. Globally, variable rates of multidrug resistance were reported in UPEC, for example, MDR rates of 62.25%, 73%, 64.9%, and 14.4% were reported in UPEC isolates from China, Iran, Nepal, and Hungary, respectively [ 3 , 10 , 18 , 59 ].…”
Section: Discussionmentioning
confidence: 83%
“…Regarding other regions in Egypt, Hassuna et al found that 62% of UPEC isolated in Upper Egypt were MDR in 2020 [ 56 ], and a recent study published in 2022 by Mohamed et al reported that 80% of UPEC were MDR in Alexandria governorate, Egypt [ 57 ]. These results reflect the increasing trend of AMR in Egypt, which is strongly linked to poor patient compliance, self-medication, and the availability of antibiotics as over-the-counter medications [ 58 ]. Globally, variable rates of multidrug resistance were reported in UPEC, for example, MDR rates of 62.25%, 73%, 64.9%, and 14.4% were reported in UPEC isolates from China, Iran, Nepal, and Hungary, respectively [ 3 , 10 , 18 , 59 ].…”
Section: Discussionmentioning
confidence: 83%
“…Defined daily doses (DDDs) and DDDs/100 or 1000 bed-days/patient days [124,[133][134][135][136][137][138][139][140] % of inpatients prescribed antibiotics/antimicrobials [27,40,86,112,114,125,126] Days of therapy per 1000 study patient days [70] Average number of antibiotics prescribed per in-patient [53] % of patients' notes where the indication for administering antibiotics is documented/stop or review dates recorded [27,53,86] % of patients prescribed antibiotics postoperatively for SAP for longer than 24 h after surgery/duration of SAP postoperatively [67,123,126,134] % Empiric prescribing vs. targeted antibiotic prescribing (following culture and sensitivity testing results) [27,86,113,114,141] % of "Access" versus "Watch" or "Reserve" antibiotics or % reduction in targeted antibiotics [44,82,137,142,143] % decreased prescribing of restricted antibiotics [144][145][146] % compliance with current guidelines [54,86,126,134,…”
Section: Activity (Process/performance) Indicatorsmentioning
confidence: 99%
“…Similar to the systematic review of Saleem et al (2020) and the recent Pan-African study [40,63], key categories included the number of participating hospitals within the PPS study, the PPS methodology, e.g., ECDC, WHO, or Global PPS, [27,112,124,176], as well as the first, second, or third most prescribed antibiotic broken down by ATC code and the AWaRe classification [47][48][49]188]-the latter, especially with growing concerns regarding the extent of prescribing of "Watch" and "Reserve" antibiotics among a number of Western and Central Asian countries [44,47,50]. In addition, whether antibiotics were prescribed for prophylaxis or treatment and the average number of antibiotics prescribed per patient.…”
Section: Current Antimicrobial Utilisation Patterns Among Hospitals A...mentioning
confidence: 99%
“…An adapted questionnaire was used composed of socio-demographic data, parents' knowledge, and attitudes toward antibiotics. An educational program consisting of a teaching session of 30 minutes covering information about antibiotics and standardized practice to teach community parents about the appropriate use of antibiotics among their children was utilized, where the education session was adopted by the World Health Organization (WHO) and the American Academy of Pediatrics, and a review of many studies that were held in Arabic countries was carried out (Ashour et al, 2022;Magdy et al, 2021;van Buul et al, 2015). The American Academy of Pediatrics and the Jordan Food and Drug Association have reviewed relevant studies with high content validity.…”
mentioning
confidence: 99%